Evaluation of Monkeypox- and Vaccinia virus-neutralizing antibodies in human serum samples after vaccination and natural infection - Manenti, Alessandro; Solfanelli, Niccolò; Cantaloni, Paolo; Mazzini, Livia; Leonardi, Margherita; Benincasa, Linda; Piccini, Giulia; Marchi, Serena; Boncioli, Martina; Spertilli Raffaelli, Chiara; Tacconi, Danilo; Mattiuzzo, Giada; et al. (Frontiers in Public Health, 2023)
Introduction: In early to mid-2022, an unexpected outbreak of Monkeypox virus infections occurred outside the African endemic regions. Vaccines originally developed in the past to protect against smallpox are one of the available countermeasures to prevent and protect against Orthopoxvirus infections. To date, there are few studies on the cross-reactivity of neutralizing antibodies elicited by previous vaccinia virus-based vaccination and/or monkeypox virus infection. The aim of this study was to evaluate a possible approach to performing monkeypox and vaccinia live-virus microneutralization assays in which the read-out is based on the production of cytopathic effect in the cell monolayer. Methods: Given the complexity of Orthopoxviruses, the microneutralization assay was performed in such a way as to uncover a potential role of complement, with and without the addition of an external source of Baby Rabbit Complement. A set of human serum samples from individuals who had been naturally infected with monkeypox virus and individuals who may have and not have undergone vaccinia virus vaccinations, was used to evaluate the performance, sensitivity, and specificity of the assay. Results and conclusions: The results of the present study confirm the presence and cross-reactivity of antibodies elicited by vaccinia-based vaccines, which proved able to neutralize the monkeypox virus in the presence of an external source of complement.